Effectiveness of Coconut Oil Massage on Weight Gain among Low Birth Weight Newborns - Jeya Singh, Evangelin Sally (International Journal of Innovative Research in Medical Science, 2017)
The birth of newborn is one of the most awe inspiring and emotional events that can occur in one's life time. Infants born at term or post term may weigh less than 2500gms is considered to be low birth weight babies. Approximately 80% of neonatal deaths and 50% of infant deaths are related to low birth weight. Aim: The aim of this study was to assess the effectiveness of coconut oil massage on weight gain among low birth weight newborns. Method: After-only with control group experimental design was adopted. Total sample size was sixty newborns. Thirty new born in experimental group and remaining thirty of them in control group. Using convenient sampling technique newborns with the birth weight of 2000 to 2500gms and the age between 8-28days were included in the study. The procedure was 20 ml of coconut oil applied to the entire body of the newborns for 2 times a day with the duration of 15 minutes to the experimental group for five days. The control group was not received the oil massage. Weight gain was assessed by electronic infant weighing scale. The data were analyzed using descriptive and inferential statistics. Results: The mean value was 4.5 with a standard deviation of 3.65 in experimental group and 2.03 mean with the standard deviation of 0.7 in the control group and the calculated’t’ value was 3.21 which shows that there was significant difference between experimental and control group at P< 0.01 level. Conclusion: The findings of the study revealed that there was a significant weight gain among low birth weight newborns who were received coconut oil massage.